The Role of Materialism and Brand Consciousness in Shaping Adolescence Life Satisfaction - Tehseen Nawaz; Saira Majid; Atif Rasool (Research Journal of Psychology, 2025)
Growing materialism and brand awareness is spreading fast in modern society and especially in the lower middle-class adolescents. The exposure to social media and the perceived symbolic worth assigned to the brands have triggered youths to perceive branded products as signals of quality, status and personal prestige. The culture change has led to increased aspect of materialism whose nature threatens to erode life satisfaction and give rise to the maladaptive behaviors. However, little empirical analysis on these relationships has been done in the local setting. This study was intended to focus on exploring the connections between materialism and brand consciousness with life satisfaction in adolescents and gender differences in the former variables. It was 300 adolescents (155 males, 145 females). Life satisfaction was measured with Satisfaction with Life Scale (Diener, 1985), brand consciousness with Consumer Style Inventory (Sproles and Kendall, 1986) and materialism as by means of Material Values Scale (Richins and Dawson, 1992). Each of the measures showed sufficient reliability. The results of the correlational analysis indicated that brand consciousness was strongly related to life satisfaction and materialism was statistically significantly related to life satisfaction. The independent samples t-test revealed materialism scores of males were much higher in comparison to females but life satisfaction and brand consciousness were the same among both genders. The results also point to the balancing effect of consumer related values on the well-being of adolescents and possible intervention in forming a balanced consumer attitude during early stages of development.